SMP domain proteins in membrane lipid dynamics - Jeyasimman, Darshini (2020)
Synaptotagmin-like mitochondrial-lipid-binding (SMP) domain proteins are evolutionarily conserved family of proteins in eukaryotes that localize between the endoplasmic reticulum (ER) and either the plasma membrane (PM) or other organelles. They are involved in tethering of these membrane contact sites through interaction with other proteins and membrane lipids. Recent structural and biochemical studies have demonstrated that SMP domain proteins transport a wide variety of lipid species by the ability of the SMP domain to harbor lipids through its unique hydrophobic cavity. Growing evidence suggests that SMP domain proteins play critical roles in cell physiology by their actions at membrane contact sites. In this review, we summarize the functions of SMP domain proteins and their direct roles in lipid transport across different membrane compartments. We also discuss their physiological functions in organisms as well as “bypass” pathways that act in parallel with SMP domain proteins at membrane contact sites.